PROSES IMPREGNASI ZnCl2 PADA PROSES PEMBUATAN KARBON AKTIF TEMPURUNG KEMIRI (ZnCl2 Impregnation Process in Production of Candellnut Shell Activated Carbon) - Sylvia, Hartina; Turmuzi, Muhamamd; Hasibuan, Rosdanelli (Jurnal Hasil Penelitian Industri, 2014)
The effect on the ZnCl2 impregnation process Candellnut shell activatedcarbon, followed by pyrolysis process. variations in the concentration used ZnCl2 2.5; 7.5;10; 15; 30%, pyrolysis temperature 450, 500, 550oC with a 90, 120 and 180 minutes. Thetesting result of iodine absorption showed the greatest results using ZnCl2 10%,temperature 4500C, for 2 hours. Without and with Candellnut shell impregnation alsoaffect the outcome of Thermal Gravimetry Analysis which use traditional impregnationwith a shift during pyrolysis temperature, operation time is marked by the occurrence ofmass loss. Shifting patterns of functional groups were analyzed using Fourier TransformInfra Red to CH aliphatic, aromatic CH, OH bond, the C=H, CN bond and the C=O. Theresult analysis of activated carbon after impregnation with Teller Brunauer Emmettmethode obtained 589 m2/g of surface area.